Parallel performance model for network processors and the characteristics of multithread stalls - SHI Xiang-quan; SU Jin-shu; CHEN Yi-jiao; WU Chun-qing (Tongxin xuebao)
The factors that impact the performance of network processors with multiprocessor and multithreading was analyzed.Then a parallel performance model--NP3M was prposed,and the primary factors that its performance depends on was discussed.Furthermore,the relationship between multiprocessor,multithreading and the whole performance of network processors was studied.Lastly,the test results about NP3M was presented.